Pelaksanaan Penyelesaian Sengketa Konsumen Melalui Jalur non Litigasi - Mairul, Mairul; Irianto, Kartika Dewi (Universitas Muhammadiyah Sumatera Barat, 2018)
The implementation of consumer dispute settlement through non-litigation channels under the Consumer Protection Act was settled at the Consumer Dispute Settlement Agency (BPK) that solved the financial services sector dispute. However, with the establishment of the Alternative Dispute Settlement Institution (LAPS) as in the form of a Financial Services Authority (OJK) specifically dealing with financial service disputes with those who are very familiar with the activities of the financial services sector, therefore how is the existence of BPSK after the formation of LAPS. The method to be used in this research is sociological juridical, because this research uses primary data such as legal material and other regulation data collection will use interview method to BPSK, LAPS, and OJK, and supported by the use of secondary data that is literature related to this research. as supporting data. Based on the results of the discussion obtained that the implementation of dispute resolution in BPSK only handled by the party appointed by the government sometimes not necessarily control the financial service disputes. While LAPS first complaint submitted to the financial services institutions. OJK requires the agency to handle the complaint. If it does not agree then the consumer can complain to the OJK or LAPS, For that, the need for synchronization of arrangements and competence of authority as a consumer dispute resolution institution between BPSK with LAPS.